Enhancing genetic variability in Trigonella species through sodium azide induction: morpho-physiological and chromosomal amelioration - Naaz, Neha; Choudhary, Sana; Hasan, Nazarul; Sharma, Nidhi; Alharbi, Khadiga; Abd El Moneim, Diaa (Frontiers in Genetics, 2024)
Plant breeding, aimed at enhancing desired traits, depends on genetic diversity. Mutation breeding is a powerful method to rapidly expand genetic diversity, facilitating crop improvement and ensuring food security. In a recent study, researchers evaluated the genetic variability of Trigonella species using different doses of sodium azide (0.2%, 0.4%, 0.6%, 0.8% and 1.0%) through morphological, physiological, and cytogenetic studies. Morphological variations were observed in cotyledonary leaves, vegetative leaves, and overall plant growth and habit. Several quantitative parameters such as plant height, fertile branches per plant, pods per plant (or cluster), seeds per pod, and seed yield showed an increase up to 0.2% and 0.4% sodium azide compared to the control. Furthermore, the total chlorophyll content and carotenoids increased up to 0.2% sodium azide over the control but decreased with higher concentrations. Scanning electron microscopy revealed that stomatal aperture and seed dimensions increased at lower concentrations of sodium azide treatment. The study found a positive correlation between the different parameters studied in the Trigonella species, as indicated by high rvalues. Based on their findings, it was concluded that the genotype of fenugreek can be improved by using 0.2% and 0.4% concentrations of sodium azide. However, the evaluation of observed variants in successive generations is a critical and necessary process to validate their potential as keystones for crop genetic improvements.